Yeast hnRNP-related proteins contribute to the maintenance of telomeres - Lee-Soety, Julia Y. (2012)
Telomeres protect the ends of linear chromosomes, which if eroded to a critical length can become uncapped and lead to replicative senescence. Telomerase maintains telomere length in some cells, but inappropriate expression facilitates the immortality of cancer cells. Recently, proteins involved in RNA processing and ribosome assembly, such as hnRNP (heterogeneous nuclear ribonucleoprotein) A1, have been found to participate in telomere maintenance in mammals. The S. cerevisiae protein Npl3 shares significant amino acid sequence similarities with hnRNP A1. We found that deleting NPL3 accelerated the senescence of telomerase null cells. The highly conserved RNA recognition motifs (RRM) in Npl3 appear to be important for preventing faster senescence. Npl3 preferentially binds telomere sequences in vitro, suggesting that Npl3 may affect telomeres directly. Despite similarities between the two proteins, human hnRNP A1 was unable to complement the lack of Npl3 to rescue accelerated senescence in tlc1 npl3 cells. Deletion of CBC2, which encodes another hnRNP-related protein that associates with Npl3, also accelerates senescence. Potential mechanisms by which hnRNP-related proteins maintain telomeres are discussed.